Model sistem dinamis industri ayam pedaging dalam memenuhi kebutuhan daging ayam - Sirajuddin Sirajuddin; Galih Bhaswara; Akbar Gunawan (Journal Industrial Servicess, 2022)
Forecasting broiler meat production is very important to avoid a deficit or lack of broiler meat availability so that the nutrition of the people of Cilegon city can be fulfilled. The Cilegon Livestock Service has a record of fluctuating chicken production every year. Data were obtained from the distribution of broiler production in the city of Cilegon. However, this does not guarantee that the amount of chicken production in Cilegon City follows the demand. For this reason, it is necessary to conduct research using the dynamic system method. The purpose of this study was to identify the factors that affect the availability of chickens, create a broiler availability system through a dynamic system, and calculate the level of chicken availability in the city of Cilegon. The results of the dynamic system simulation show that the research shows that in 2022-2026 the demand for broilers is experiencing an increasing trend, but the production of broilers is in deficit. In the years 2022-2026, the demand for chicken meat is increasing and the availability is insufficient with a very significant difference. Therefore, through this research, the Cilegon City Government must increase the production of broilers in Cilegon City by increasing the number of breeders and opening up import opportunities from other cities so that the needs of broilers in Cilegon City can be fulfilled.